Mekanika gelombang dalam koordinat kurvelinear= Wave Mechanics in Curvilinear Coordinates - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
INTISARI Disajikan cara yang sederhana untuk membentuk wakilan mekanika kuantum di ruang Hilbert dengan menggunakan basis kontinu yang merupakan eigenkeadaan perangkat operator koordinat Cartesan dan kurvelinear ortogonal yang sating berkomutasi. Dengan menggunakan asas-asas mekanika kuantum dan teori wakilan dalam ruang Hilbert mulai dari wakilan dalam koordinat Cartesan, dihasilkan mekanika getombang dalam koordinat Cartesan dan kurvelinear. Wakilan koordinat berbagai operator dinamik balk yang memuat koordinat atau momentum kanonisnya, maupun yang memuat kedua perangkat observabel yang berjodoh kanonis tersebut, diturunkan bentuk eksplisitnya dalam sistem koordinat kurvelinear ortogonal. Hasilnya dibandingkan dengan bentuk baku yang ada disertai pembahasan beberapa permasalahan terkait. Keinvarianan tera persamaan SchrUdinger gayut waktu untuk muatan yang bergerak dalam medan elektromagnet ( E, B) ditinjau dalam sistem koordinat kurvelinear dideduksikan secara sederhana. Kara kanci : Mekanika Kuantum, Mekanika Gelombang, Koordinat Kurvelinear. ABSTRACT A simple method for constructing a representation of quantum mechanics in Hilbert space using a continuous basis produced from eigenstates of a commuting set of Cartesian and orthogonal curvilinear coordinate operators is presented using quantum mechanics principles as well as the representation theory in Hilbert space starting from a representation in a Cartesian coordinates system. This construction generates wave mechanics in curvilinear coordinates. The representation of various dynamical operators containing either coordinates or canonical momenta as well as those containing both set of the canonically conjugate observables, are derived for their explicit forms in orthogonal curvilinear coordinates system. The results are compared with standard forms and some related problems are discussed. The gauge invariance of the time dependent SchrUclinger equation for a charged particle moving in an electromagnetic Field ( E,B ) referred to a curvilinear coordinates system is conveniently deduced. Key words : Quantum Mechanics, Wave Mechanics, Curvilinear Coordinates.